‘Abd al-Wahhāb ibn Ja‘far ibn al-Maydānī (Died 418 AH / 1027 AD) And His Book on History - Okleh, Issam; Chatra, Khireddine Youssef (Jordan Journal for History and Archaeology, 2022)
This study examines the Damascene historian ‘Abd al-Wahhab ibn Ja‘far, known as Ibn al-Maydani (d. 418 AH / 1027 AD), and his book on the history of Damascus, by covering his life, and demonstrating the importance of his work as one of the few Damascene historians who were contemporary to the beginnings of the rule of the Fatimid state in the Levant. The study sheds light on his life and culture and studies the surviving portions of his book, his method of organization, the sources he relied on, his methodology, the temporal scope of the book and its importance for the history of Damascus and Fatimid studies in general. The book can be classified as a history of Damascus. Ibn al-Maydani’s methodology was based on accurately presenting the history of each year and its events by day, time, month and year. He organizes his information in terms of accession and removal of the rulers. His book became an essential source for everyone who came after him.